Cloud‐Resolving Model Intercomparison of an MC3E Squall Line Case: Part II. Stratiform Precipitation Properties. Issue 2 (29th January 2019) - Han, Bin; Fan, Jiwen; Varble, Adam; Morrison, Hugh; Williams, Christopher R.; Chen, Baojun; Dong, Xiquan; Giangrande, Scott E.; Khain, Alexander; Mansell, Edward; Milbrandt, Jason A.; Shpund, Jacob; et al.
Abstract: In this second part of a cloud microphysics scheme intercomparison study, we focus on biases and variabilities of stratiform precipitation properties for a midlatitude squall line event simulated with a cloud‐resolving model implemented with eight cloud microphysics schemes. Most of the microphysics schemes underestimate total stratiform precipitation, mainly due to underestimation of stratiform precipitation area. All schemes underestimate the frequency of moderate stratiform rain rates (2–6 mm/hr), which may result from low‐biased ice number and mass concentrations for 0.2–2‐mm diameter particles in the stratiform ice region. Most simulations overestimate ice water content (IWC) at altitudes above 7 km for temperatures colder than −20 °C but produce a decrease of IWC approaching the melting level, which is opposite to the trend shown by in situ observations. This leads to general underestimations of stratiform IWC below 5‐km altitude and rainwater content above 1‐km altitude for a given rain rate. Stratiform precipitation area positively correlates with the convective condensate detrainment flux but is modulated by hydrometeor type, size, and fall speed. Stratiform precipitation area also changes by up to 17%–25% through alterations of the lateral boundary condition forcing frequency. Stratiform precipitation, rain rate, and area across the simulations vary by a factor of 1.5. This large variability is primarily a result of variability in the stratiform downward ice mass flux, which is highly correlated with convective condensate horizontal detrainment strength. The variability of simulated local microphysical processes in the stratiform region plays a secondary role in explaining variability in simulated stratiform rainfall properties. Plain Language Summary: This is a unique model intercomparison study about different microphysics parametrizations commonly used, with the purposes of examining model biases and variability as well as identifying major factors/processes leading to bias and variability. The study simulated a well‐observed squall line MCS from MC3E field campaign, and focused on the stratiform precipitation, following on our part 1 study focusing on convective part. We employed a more constrained approach compared with past intercomparison studies to better identify processes contributing to the differences. Another unique part is our comprehensive model evaluation, that is, we identify stratiform columns and evaluate vertical evolution of cloud properties including size distribution. We find that most of the microphysics schemes underestimate total stratiform precipitation, mainly due to underestimation of stratiform precipitation area. Moderate stratiform rain rates are underestimated, mainly due to incorrect vertical evolution of ice particles. Stratiform precipitation properties across the simulations vary by a factor of 1.5, primarily a result of variability in detrained condensate amount. In addition, we find that stratiform precipitation area correlates well with detrainment amount and is modulated by the detrained hydrometeor properties. So convective microphysics plays a key role in determining stratiform properties. Key Points: Underestimation of total stratiform precipitation in most simulations is mainly due to underestimation of stratiform precipitation area Low‐biased rainwater content is caused by low‐biased stratiform ice water content below 5‐km altitude for a given rain rate Simulated stratiform precipitation variability is correlated with variability in the convective condensate being detrained